A Study on Entrepreneurial Attitude Among Technical Graduates - Shani, N. (Prabandhan: Indian Journal of Management, 2011)
Entrepreneurship has been recognized as an important element in the dynamics of modern economies. This impressive and rapid growth of entrepreneurship is attributed to the power of education in promoting social, economic, political, and spiritual well-being of an individual and social development. The growth of entrepreneurship programs in educational institutions has been remarkable for over two decades, and is now aimed to change the mindset of the youth. The training should aim at initiating and accelerating the process of entrepreneurship development through inculcating an entrepreneurial culture. To obtain the required results in the training activities, attention must also be paid to the development of an environment where entrepreneurial activities can flourish and grow. This paper, while examining various factors and ways to improve the entrepreneuship in our country, focuses on the influence of Education and Training, which is one of the major Entrepreneurial Framework Conditions, in promoting Entrepreneurship.